Tobacco smoking and survival after a prostate cancer diagnosis: A systematic review and meta-analysis - Darcey, E.; Boyle, Terry (W B Saunders co Ltd, 2018)
© 2018 Elsevier Ltd Background: While a number of studies indicate tobacco smoking has a detrimental impact on survival and recurrence after a prostate cancer diagnosis, there has been no quantitative review of this literature and it is unclear whether tobacco smoking affects clinical populations differentially. We conducted a systematic review and meta-analysis to investigate the associations between tobacco smoking and overall (OM) and prostate cancer-specific (PSM) mortality and recurrence after a prostate cancer diagnosis. Methods: EMBASE and ISI Web of Science were searched for English-language studies, published up to August 17, 2017, which conducted a survival analysis to estimate the association between tobacco smoking and OM, PSM and/or recurrence. A random-effects meta-analysis was conducted to estimate the summary hazard ratios (HRs) for the associations between tobacco smoking and the three outcomes. Results: A total of 28 studies met the inclusion criteria. The results of the primary meta-analysis indicate current smokers have significantly poorer overall survival (Summary HR = 1.96, 95% CI = 1.69, 2.28), prostate cancer-specific survival (Summary HR = 1.79, 95% CI = 1.47, 2.20) and recurrence-free survival (Summary HR = 1.48, 95% CI = 1.28, 1.72) than never smokers. Similar results were found in population-based studies and in studies conducted in specific clinical populations. Conclusions: The results of this systematic review and meta-analysis indicate that tobacco smoking at prostate cancer diagnosis is associated with a significantly increased risk of overall mortality, prostate-cancer specific mortality and recurrence. We recommend future studies collect more detailed information about tobacco smoking to further understanding of the association between tobacco smoking and PCa prognosis. In addition, further research should concentrate on the impact of smoking cessation post-diagnosis and post-treatment on prognosis, and the feasibility and effectiveness of smoking cessation programs.